Histomorphometric study of the human spleen - Alim, Abdul; Nurunnabi, Abu Sadat Mohammad; Mahbub, Sabiha; Ara, Shamim (Bangladesh Journal of Medical Science, 2012)
Context: The spleen is the largest single mass of lymphoid tissue in all vertebrates. Histological changes are evident in advancing age along with functional capability of the human spleen. A cross-sectional, descriptive type of study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from January to December 2008, to see the age related microscopic changes in the human spleen. Methods: 30 human spleens were collected from the unclaimed dead bodies that were under examination in the Department of Forensic Medicine of Dhaka Medical College, Dhaka. The samples were divided into three age-groups including group A (15-29 years), group B (30-49 years) & group C (50-69 years). Then 5 best prepared histological slides from each group were taken and examined under the light compound microscope to determine the thickness of capsule, diameter, number and percent amount of white pulp in the human spleen. Results: The thickness of the splenic capsule were found 84.60±7.97 ?m, 117.92±4.16 ?m, and 132.17±6.37 ?m in group A, B and C respectively. The diameter of the white pulp were found 0.32±0.01 mm, 0.32±0.01 mm and 0.31±0.01 mm, while the number of white pulp per sq. mm were 2.28±1.04, 2.38±0.93 and 2.04±0.76 in group A, B and C respectively. Moreover, the amounts of the white pulp were determined 23.09±1.38, 24.45±1.84 and 22.54±1.08 in group A, B and C respectively. The difference in thickness of the splenic capsule was statistically significant among the study groups (p<0.001). However, no difference was found in diameter, number and percentage of the white pulp of the spleen among those age groups. Conclusion: The thickness of the capsule of the spleen was found to increase with advancing age in humans. However, no age change was evident in diameter, number or amount of the white pulp. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12600 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12